Revisiting heat treatments for additive manufactured parts: A case study of A20X alloy. (January 2023) - Barode, Jayant; Vayyala, Ashok; Virgillito, Enrico; Aversa, Alberta; Mayer, Joachim; Fino, Paolo; Lombardi, Mariangela
Graphical abstract: Highlights: Post-processing T7 heat treatment and microstructural evolution of laser powder fused A20X alloy was investigated. T7 offers undissolved θ-Al2 Cu phase near TiB2 particles and promotes early precipitate free zones formation upon aging. A novel short and simple heat treatment was proposed for the improved mechanical behaviour. Exceptional improvement (̴ 45%) in the tensile ductility was achieved with respect to T7. Abstract: A20X (Al-Cu-Ag-Mg-TiB2 ) is a precipitation hardening alloy, recently developed for additive manufacturing processing. Printed parts of A20X alloy are usually post-processed with a long T7 heat treatment for improved mechanical properties with respect to its as-built counterparts. However, in the present investigation, it was demonstrated that T7 might not be the best suitable heat treatment available for A20X alloy. A detailed microstructural characterization of A20X samples processed with laser powder bed fusion and post-processed with T7 was carried out. Microstructural features were analysed in terms of grain size, precipitate size, phase quantification, dislocation density and width of the precipitate free zones. After the analysis, a simple and rapid heat treatment was proposed which significantly improved the mechanical properties. The yield strength (YS), ultimate tensile strength (UTS) and elongation to fracture (e) for the T7 heat treatment were 370 ± 9 MPa, 435 ± 13 MPa and 7.3 ± 0.3 % respectively. With the proposed heat treatment, an increment of 7.1 % in YS, 6.3 % in UTS and 45 % in e was witnessed. This exceptional improvement in the mechanical behaviour has been associated with the absence of grain boundary cracking in the proposed heat treatment.